MANAGEMENT STRATEGY IN IMPROVING QUALITY EDUCATION AT SYARIF HIDAYATULLAH HIGH SCHOOL - Habibullah, Naufal Fahmi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Strategic management has an important role in improving the quality of education. This study aims to find out: (1) How is strategic planning in improving the quality of education in SMA Syarif Hidayatullah (2) How is strategic management implemented in improving the quality of education in SMA Syarif Hidayatullah (3) How is strategic management evaluating in improving the quality of education in SMA Syarif Hidayatullah .This research is a descriptive qualitative research, data collected through observation, interviews, documentation, triangulation, and analyzed using descriptive analysis techniques. This study aims to determine the process of planning, implementing, and evaluating strategic management in improving the quality of education at SMA Syarif Hidayatullah. In the study of strategic management in improving the quality of education at Syarif Hidayatullah High School, it shows that: (1) Strategic planning at Syarif Hidayatullah High School includes four activities, namely developing vision, mission and goals, short, medium and long term planning, identification of internal factors and external, as well as strategy formulation. (2) The implementation of strategic management at Syarif Hidayatullah High School includes four activities, namely determining madrasah policies, motivating educators and education staff, allocating human resources, and developing a strategic culture. (3) Evaluation of strategic management at Syarif Hidayatullah SMA includes three activities, namely monitoring all results, measuring individual and madrasah performance, taking corrective steps.